Pemodelan Sistem Antrian Klinik Kesehatan XYZ pada Dokter Spesialis dengan menggunakan Flexsim - Riski Arifin; Rafi Dio (Jurnal Bhara Petro Energi, 2022)
Health services are things that must be considered by minimizing the occurrence of queuing time and providing maximum service. XYZ health clinic provides specialist doctors and pharmacies to community services. There are four main activities in the XYZ health clinic, namely registration, doctor services, pharmacy services and payments. This study simulated a queuing system using flexsim to see how many queues there were and the waiting time. The results showed that the lowest idle percentage was in doctor's services at 8.2%, and the highest percentage of working processing was 91.8%. Then for a queue of 3 people and a waiting time of 19.5 minutes waiting for a doctor's service and the number of patients handled is 13-15 people. Adding a scenario by adding a new doctor by conducting a comparative test does not make a difference in the number of patients treated.